Knowledge networks innovation through communities of practice - Hildreth, Paul M., 1959-; Kimble, Chris; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2004)
This book draws on the experience of people who have worked with CoPs and presents their combined wisdom in a form that is accessible to a wide audience. CoPs are examined from a practica view. The book also examines the benefits that CoPs can bring to an organization, provides a number of case studies, lessons learned and sets of guidelines. It also looks at virtual CoPs and to the future by asking 'what next?'
Building Sustainable Communities of Practice / Bronwyn Stuckey and John D. Smith -- How Information Technologies Can Help Build and Sustain an Organization's CoP: Spanning the Socio-Technical Divide? / Laurence Lock Lee and Mark Neff -- Building a Community of Practice: Technological and Social Implications for a Distributed Team / Pete Bradshaw, Stephen Powell and Ian Terrell -- Facilitator Toolkit for Building and Sustaining Virtual Communities of Practice / Lisa Kimball and Amy Ladd -- The Use of Intranets: The Missing Link Between Communities of Practice and Networks of Practice? / Emmanuelle Vaast -- Extending Richness with Reach: Participation and Knowledge Exchange in Electronic Networks of Practice / Robin Teigland and Molly McLure Wasko -- Trusting the Knowledge of Large Online Communities: Strategies for Leading from Behind / John S. Storck and Lauren E. Storck -- Double Agents: Visible and Invisible Work in an Online Community of Practice / Elisabeth Davenport -- Cultivating a Public Sector Knowledge Management Community of Practice / Shawn Callahan -- Click Connect and Coalesce for NGOS: Exploring the Intersection Between Online Networks, CoPs, and Events / Nancy White -- Where Did That Community Go? Communities of Practice That "Disappear" / Patricia Gongla and Christine R. Rizzuto.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 28, 2010).
Keywords: Knowledge management; Organizational learning; Electronic books